2021
DOI: 10.1111/jocs.15462
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of off‐pump coronary artery grafting for patients with impaired left ventricular ejection fraction: A retrospective cohort study from a single institutional database

Abstract: Objective Despite substantial advances in surgical practice, the management of patients with impaired left ventricular ejection fraction (LVEF) remains challenging. Furthermore, evidence on the outcomes of off‐pump coronary artery bypass (OPCAB) surgery in this population is inconsistent. We conducted the present study to compare the short‐ and long‐term outcomes of OPCAB in patients with different ejection fractions. Methods This retrospective cohort study used data from the Hua‐Shan Cardiac Surgery and inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The safety and efficacy of off-pump coronary artery bypass (OPCAB) surgery in patients with reduced ejection fraction have not fully understood. Jiang et al 1 demonstrated that OPCAB was safe and effective regarding short-term and long-term clinical outcomes irrespective of the levels of left ventricular ejection fraction. Several concerns have been raised.…”
Section: Off-pump Coronary Artery Grafting In Patients With a Reduced Ejection Fractionmentioning
confidence: 99%
“…The safety and efficacy of off-pump coronary artery bypass (OPCAB) surgery in patients with reduced ejection fraction have not fully understood. Jiang et al 1 demonstrated that OPCAB was safe and effective regarding short-term and long-term clinical outcomes irrespective of the levels of left ventricular ejection fraction. Several concerns have been raised.…”
Section: Off-pump Coronary Artery Grafting In Patients With a Reduced Ejection Fractionmentioning
confidence: 99%